The Value of Religious Tolerance in the Interpretation of the Qur'an and its Relevance in Learning in Higher Education - Abdullah Mahmud (International Journal of Social Service and Research, 2023)
·       This paper tries to reveal the values of tolerance in the Qur'an through the interpretation of The Glorious Kur'an by Yousuf Ali and The Message of Qur'an by M. Asad. After an in-depth study of the verses that are the focus of study in the two works of interpretation, the author finds values of tolerance such as, prohibition against denouncing the deities of other religions, prohibition of degrading people of other religions, may dialogue/debate with followers of other religions, freedom of religion, prohibition of forcing others to follow religion, belief, religious law, or moral law that we believe, do not hate followers of other religions,  and always huznudzan against them, as well as acknowledging the existence of other religions. After finding the values of tolerance above, the author tries to reveal the relevance of these values to the learning of Al-Islam and Kemuhammadiyahan (AIK) at the University of Muhammadiyah Surakarta (UMS) through field research. Field data were obtained through observation and interviews. Broadly speaking, AIK learning at UMS can be categorized into three learning models: 1. Baitul Arqam: semesters 1-2 (for Muslim students), 2. Classical Learning: semesters 1-2 (specifically for non-Muslim students), 3. Classical Learning: semesters 3-4 (for Muslim and non-Muslim students). After in-depth research, it was found that the various tolerance values mentioned above are in accordance with AIK learning at UMS.